A class of Julia exceptional functions - Khoroshchak, V.S.; Khrystiyanyn, A.Ya.; Lukivska, D.V. (Carpathian Mathematical Publications, 2016)
The class of p-loxodromic functions (meromorphic functions, satisfying the condition f(qz) = pf(z) for some q C{0} and all z C{0}) is studied. Each p-loxodromic function is Julia exceptional. The representation of these functions as well as their zero and pole distribution are investigated.